The E2 admixture in mixed multipole line 647.6 nm in the spectrum of Bi I - Werbowy, S.; Kwela, J. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
A study of the hyperfine structure of mixed multipole line 646.7 nm of Bi I is reported. A special computer program was designed to obtain the predicted contour of the hyperfine structure of the line for different values of the electric-quadrupole admixture. By variation of free parameters, describing the line shape and the electric-quadrupole admixture D, defined as the ratio of the magnetic-dipole and electric-quadrupole decay rates D = AE2/(AM1 + AE2), the calculated profiles were fitted into the recorded spectra. The D value of the best fit found is (17.8 ± 1.0)%. Our result is compared with recent theories and other experiments.
Optica Applicata, Vol. 36, 2006, nr 4, s. 535-541
Keywords: optyka; hyperfine structure; forbidden transitions; transition probability